Transient Parameter Analysis of Non-scrammed Local Melting Accidents—A VVER 1000 Case Study - Salmassian, Behzad; Rabiee, Ataollah; Nematollahi, Mohammad R.; Faghihi, Farshad; Pirouzmand, Ahmad (Frontiers in Energy Research, 2021)
The first stage of a core degradation- based on the defense-in-depth concept of nuclear power plant (NPP) safety is partial fuel melting due to local blockage. The flow blockage accidents with no SCRAM happening can lead to a local fuel-clad failure, consequently affecting the safety of NPP. The present study provides an analysis of Anticipated Transient Without SCRAM (ATWS) which might lead to burning out condition. The accidents related to ATWS scenarios, detailed in the case of VVER-1000/V446 reactor FSAR (Final Safety Analysis Report), include pump failure, local blockage, relative power increase, and a combination of these transients. In this research, first, drawing upon MCNPX 2.7 and COBRA-EN codes, a coupling framework is developed and then validated using an authentic reference point. The obtained results reveal that the reactor SCRAM does not occur while accidents are being investigated as there are a 10% difference in the mass flow rate reduction, a 470 kPa in the channel pressure drop, and a 204°K in the clad temperature, which constitute limitations under most pessimistic scenarios. However, under these conditions, a 70% void fraction during 12 minutes is observed in certain channels. Hence, burn out and local fuel melting could occur under normal operational and ATWS circumstances. According to uncertainty analyses, the occurrence of the void fraction above zero is locally definite. The transient analysis outputs could be deployed as monitoring system inputs and exploited for identifying weak points in the system.